Comparison of a Neutral Density Model With the SET HASDM Density Database. Issue 12 (27th December 2021) - Weimer, Daniel R.; Tobiska, W. Kent; Mehta, Piyush M.; Licata, R. J.; Drob, Douglas P.; Yoshii, Jean
Abstract: The EXospheric TEMperatures on a PoLyhedrAl gRid (EXTEMPLAR) method predicts the neutral densities in the thermosphere. The performance of this model has been evaluated through a comparison with the Air Force High Accuracy Satellite Drag Model (HASDM). The Space Environment Technologies (SET) HASDM database that was used for this test spans the 20 years 2000 through 2019, containing densities at 3 hr time intervals at 25 km altitude steps, and a spatial resolution of 10° latitude by 15° longitude. The upgraded EXTEMPLAR that was tested uses the newer Naval Research Laboratory MSIS 2.0 model to convert global exospheric temperature values to neutral density as a function of altitude. The revision also incorporated time delays that varied as a function of location, between the total Poynting flux in the polar regions and the exospheric temperature response. The density values from both models were integrated on spherical shells at altitudes ranging from 200 to 800 km. These sums were compared as a function of time. The results show an excellent agreement at temporal scales ranging from hours to years. The EXTEMPLAR model performs best at altitudes of 400 km and above, where geomagnetic storms produce the largest relative changes in neutral density. In addition to providing an effective method to compare models that have very different spatial resolutions, the use of density totals at various altitudes presents a useful illustration of how the thermosphere behaves at different altitudes, on time scales ranging from hours to complete solar cycles. Plain Language Summary: A recently developed computer model predicts the mass density of atoms and molecules in upper atmosphere, in the region known as the thermosphere. Changes in this "neutral density" following geomagnetic storms can perturb the orbits of the many satellites in this region, leading to imprecise knowledge of their paths and risk of collisions. This model uses measurements of the solar wind and the embedded magnetic field to predict the level of heating in the upper atmosphere, and the resulting expansion of the atmosphere to higher altitudes. In order to test the capabilities of the new model, its calculations were compared with density values derived by an Air Force data assimilation system based on radar tracking of multiple objects in Earth orbit over a 20‐year period. The results of this comparison show an excellent agreement, particularly at the higher altitudes where geomagnetic storms have the greatest influence. Key Points: Thermosphere neutral densities from the EXospheric TEMperatures on a PoLyhedrAl gRid (EXTEMPLAR) model are compared with the SET HASDM density database for a 20 year time period The use of mean densities on spherical shells at several altitudes is an effective way to compare the models The EXTEMPLAR model performs well at altitudes of 400 km and above where geomagnetic storms produce the largest changes in neutral density